Factors Affecting the Event of The Mioma Uteri in Aceh Tamiang District Year 2018 - Martina, Martina; Santoso, Heru; Resti, Suci Nanda (Sari Mutiara Indonesia University Press, 2018)
Myoma is a reproductive disease which contributes to mortality score of women besides of pregnancy problem and childbearing in the reproductive period of women. Prevalence of myoma is 25-50% of mortality score. This disease is in the second level of mortality score after cervical cancer disease. There are many risk factors of myoma disease and we can anticipate it to minimize the death because of myoma disease. This research aims to know the faktors which influence Uterine Myoma disease at RSUD Aceh Tamiang. Kind of this research is descriptive analysis research. In this research, the Researcher used cross sectional design. Moreover, the researcher took the respondent as many as 34 people. The researcer used the questionnaires to collect the data started from 20 until 30 July 2018 at RSUD Aceh Tamiang. The result of the hypothesis showed us the influence of historical age (p=0,012), the parity (p=0,029), and the historical family (p=0,024) toward myoma disease but it did not related to the menarche factors (p=0,308), the body mass index (p=0,283), the diet pattern (p=0,500), the menstrual status (p=0,605), the historical contraception (p=0,313) toward myoma disease at RSUD Aceh Tamiang. The researcher proposes this research to be the information to maximize the services, facilities, and to expand the knowledge in education.